Maturogenesis of a Cariously Exposed Immature Permanent Tooth using Calcium Hydroxide for Pulpotomy Treatment: A Case Report - SM Abdul Quader; Iqbal Bahar; KM Rownak Jahan (Update Dental College, 2013)
With all aseptic precaution successful pulpotomy treatment of cariuosly exposed permanent teeth with reversible pulpitis and incomplete apex formation can prevent the need for root canal treatment. A case report is presented which demonstrates the use of pulpotomy with calcium hydroxide in order to achieve apexogenesis and the teeth were restored with glass ionomer cement. Clinical and radiographic follow up demonstrated a vital pulp and physiologic root development in comparison with the contra lateral tooth. DOI: http://dx.doi.org/10.3329/updcj.v1i2.13982 Update Dent. Coll. j. 2011: 1(2): 21-24